The Effect of Recycled Waste Glass as a Coarse Aggregate on the Properties of Portland Cement Concrete and Geopolymer Concrete - Jhutan Chandra Kuri; Anwar Hosan; Faiz Uddin Ahmed Shaikh; Wahidul K. Biswas (Buildings, 2023)
A significant amount of waste glass is generated in Australia and around the world, which requires sustainable recycling. The use of recycled glass as aggregates in concrete is one of the many options for recycling. This study investigated the characteristics of ordinary Portland cement (OPC) and geopolymer concretes containing different proportions of recycled glass as a partial replacement of natural coarse aggregate. It was found that the 28-day compressive and tensile strengths of OPC concrete decreased up to 21%, and 7% and of geopolymer concrete decreased by 11–26% and 11–29% with the increase in the recycled glass coarse aggregate. The porosity, sorptivity and chloride permeability of OPC and geopolymer concrete increased and the drying shrinkage decreased due to the use of the recycled glass coarse aggregate. The microstructural analysis revealed the porous interfacial transition zone (ITZ) between the glass coarse aggregate and the paste/mortar matrix led to a decrease in the strength and an increase in the porosity, sorptivity and chloride permeability of the concrete due to the increase in the glass coarse aggregate. However, the mechanical and durability properties of OPC and geopolymer concrete containing 10 to 20% glass coarse aggregate were comparable to the corresponding properties of the control concrete sample containing a natural coarse aggregate.